2014
DOI: 10.4028/www.scientific.net/msf.782.133
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of 7CrMoVTiB10-10 Steel after Heat Treatment

Abstract: Steel 7CrMoVTiB10-10 is a Cr-Mo medium alloy steel with addition of vanadium and titanium as microalloying elements and with further addition of boron. The resulting microstructure after the heat treatment takes the form of a tempered bainite. In hot rolling of seamless tubes using this particular steel grade, it is very important to find the optimum heat treatment parameters in order to obtain the final mechanical properties according to STN EN 10216-2+A2. In this paper, various optimization concepts regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Microstructural evolution and mechanical properties of T24 steels during long-term ageing and/or creep exposure have been widely studied by many authors [10][11][12][13][14][15][16]. These studies revealed precipitation of several secondary phases in T24 base materials and their welded joints such as MX, M 2 C, M 6 C, M 7 C 3 , and M 23 C 6 , where M stands for various metallic elements, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Microstructural evolution and mechanical properties of T24 steels during long-term ageing and/or creep exposure have been widely studied by many authors [10][11][12][13][14][15][16]. These studies revealed precipitation of several secondary phases in T24 base materials and their welded joints such as MX, M 2 C, M 6 C, M 7 C 3 , and M 23 C 6 , where M stands for various metallic elements, e.g.…”
Section: Introductionmentioning
confidence: 99%